Large vocal polyp causing dyspnea to young patient - Saini, Saurabh; Khan, Saquib Reyaz; Singhal, Vanshika (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2024)
The vocal cords are primarily responsible for voice production and the risk factor for non-neoplastic vocal fold lesions is usually multifactorial, laryngeal trauma (endotracheal intubation), hypothyroidism, cigarette smoking, alcohol abuse, gastroesophageal reflux (GERD) and also including phonotrauma etc. we report a 30-year-old female presented with the complaint of dyspnea and hoarseness of voice. endoscopic examination showing, the very large vocal cord polyp was seen to be arising from the left vocal cord, partially blocking the glottic chink, with minimal residual airway. ML Scopy excision of the polyp was done and size was approximately 1.5 cm.